Kelayakan dan Pratikalitas Web Kudolar Berbasis Android terhadap Kemampuan Siswa Menganalisis Dinamika Atmosfer - Tasya Wulandari; Erna Juita; Momon Dt. Tanamir (Horizon, 2022)
The function and use of information and communication technology (ICT) for education has become an irresistible need, information and communication technology in education will function as a storehouse of knowledge. This study aims to determine the analysis, feasibility and practicality of the android-based kudolar web learning media on atmospheric dynamics material and its impact on the life of class X IPS SMAN 2 Bayang. Types of research and development (Research and Development). Using a 4D model consisting of 4 stages, namely 1) Define 2) Design, 3) Development, 4) Desiminate. The subjects in this study were 116 students of class X Social Sciences. The results of the study found that: a) The appropriate learning media based on Android was declared very feasible after analyzing data processing using Microsoft Excel so that a total of 392 were obtained with an average level of 4.56 and a percentage level of 91% in the "very good" category. b) The appropriate learning media based on Android is declared practical after processing the research obtained from the questionnaire, and a practicality test is carried out so that a score of 2786 is obtained with an average level of 4.65 and a percentage of 93% in the "Practical" category.